Analisis Interaksi Antar Komponen Ekosistem Pesisir Pantai Lombang sebagai Sumber Belajar IPA SMP - Wardah Fitriyani; Farah Lailatul Nur Alifiyah; Ifa Rahmawati; Isna Silfiatul Ismawati (Journal of Progressive Science Education, 2026)
Science learning at the junior secondary level requires the integration of real environmental contexts to help students understand ecosystem concepts meaningfully rather than abstractly. Coastal areas represent dynamic environments where biotic and abiotic components interact visibly and continuously. This study aims to analyze the interactions among ecosystem components in the coastal area of Pantai Lombang and to examine its potential as a learning resource for junior high school science, particularly on ecosystem topics. This research employed a descriptive qualitative approach. Data were collected through field observations and documentation of biotic and abiotic components found in the coastal ecosystem. The analysis involved identifying ecosystem components, classifying the types of interactions occurring among them, and mapping the findings to the junior high school science curriculum. The results indicate that the coastal ecosystem of Pantai Lombang demonstrates various interactions, including biotic–biotic and biotic–abiotic relationships, which reflect key concepts such as ecosystem components, trophic interactions, and environmental balance. Therefore, the site has strong potential to be utilized as a contextual, environment-based learning resource to support science instruction at the junior secondary level.